OPTICAL COHERENCE TOMOGRAPHY IN DIAGNOSTICS OF OPTIC NERVE DISEASES - Dilfuza Zuhridinovna, Jalalova; Abbos, Olimov (PT. Antis International Publisher, 2025)
Objective: To evaluate the efficacy of optical coherence tomography (OCT) in detecting early-stage eye diseases by providing high-resolution images of critical eye structures, including the retina, lens, and optic nerve. Methods: The study highlights the use of OCT during routine eye examinations to monitor asymptomatic changes in individuals, particularly those over 35 years old, when age-related structural changes in the eye are more prevalent. Results: OCT delivers detailed imaging of eye tissues, enabling clinicians to identify minor abnormalities that are imperceptible during standard examinations. This capability enhances early detection rates for conditions that develop without visible symptoms. Annual eye exams combined with OCT are particularly valuable for detecting early markers of potentially severe diseases. Novelty: This study underscores the critical role of OCT in preventive ophthalmology, emphasizing its unmatched precision in diagnosing age-related changes in eye structures before symptoms manifest, thus bridging the gap between routine check-ups and advanced diagnostic procedures.